(y-6)(y-4)=

Simple and best practice solution for (y-6)(y-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y-6)(y-4)= equation:


Simplifying
(y + -6)(y + -4) = 0

Reorder the terms:
(-6 + y)(y + -4) = 0

Reorder the terms:
(-6 + y)(-4 + y) = 0

Multiply (-6 + y) * (-4 + y)
(-6(-4 + y) + y(-4 + y)) = 0
((-4 * -6 + y * -6) + y(-4 + y)) = 0
((24 + -6y) + y(-4 + y)) = 0
(24 + -6y + (-4 * y + y * y)) = 0
(24 + -6y + (-4y + y2)) = 0

Combine like terms: -6y + -4y = -10y
(24 + -10y + y2) = 0

Solving
24 + -10y + y2 = 0

Solving for variable 'y'.

Factor a trinomial.
(4 + -1y)(6 + -1y) = 0

Subproblem 1

Set the factor '(4 + -1y)' equal to zero and attempt to solve: Simplifying 4 + -1y = 0 Solving 4 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1y = 0 + -4 -1y = 0 + -4 Combine like terms: 0 + -4 = -4 -1y = -4 Divide each side by '-1'. y = 4 Simplifying y = 4

Subproblem 2

Set the factor '(6 + -1y)' equal to zero and attempt to solve: Simplifying 6 + -1y = 0 Solving 6 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 0 + -6 -1y = 0 + -6 Combine like terms: 0 + -6 = -6 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6

Solution

y = {4, 6}

See similar equations:

| f(x)=3x-2x^2+3 | | -6y+24-6y+9=-y+5+5y | | 5x^2+15=51 | | m+m+6+(m+6)*3=89 | | 2+3x+5x=18+5 | | 3e-6=-2e-4-7 | | 9k^2-12-1=0 | | 2+3x+5=18+5 | | f(x)=3x^2-6x+2 | | -11.2+8.4+4q=-0.08 | | 6a+8=-2a+8 | | 390-60x=578-100x | | 23-14=3(x-1) | | .87x=.5x+.75x | | 1/8*8/37= | | 2/3x-3/2x-1=5/6 | | 500=200(1+x) | | 500=200(1+x)5 | | 3/8x-50 | | 2-20/5x3 | | -(5x-11)+4(5x+7)= | | 6x^2-12=-2x | | 5x^2/x^3-x^3 | | 3z+2(-5z)+6= | | (3m-4)(2m+5)=0 | | 4+ln(x+3)=3 | | 8z-0.6=9z | | 5y-6=6y-1 | | -5j+(-2)+3= | | y--9=3/4(x-5) | | 2z+6=4z-3 | | =2u^10v^9w^8*w*9v^2*4u^9 |

Equations solver categories